Correlation of Contributing Factors with Post- Endoscopic Trans-Sphenoid Surgery Clinical Outcomes of Patients with Pituitary Adenoma - Afsoun Seddighi; Seyed Amin Nicksirat; Amir Saied Seddighi; Sally Mahmoudzadeh; Yasaman Arjmand; Anahid Nabavi; Tohid Emami Meybodi (Men's Health Journal, 2020)
Introduction: Pituitary adenomas are commonly benign, slow-growing tumors that arise from cells in the pituitary gland and consist of a common type of intracranial space-occupying lesions. Based on the functionality and size of the adenoma, both medical and surgical approaches have been described. In this study, the authors aim to determine the effects of contributing factors of patients with pituitary adenoma undergoing trans-sphenoidal endoscopic surgery to their postoperative clinical status. Material and Methods: From March 2015 to November 2016, 100 patients diagnosed with pituitary adenoma confirmed by Magnetic Resonance Imaging (MRI) underwent a trans-sphenoidal endoscopic approach in the department of Neurosurgery of Shohada Tajrish Hospital. Demographic data, as well as pre-defined relevant contributing factors regarding clinical status, were recorded. All patients underwent neuroimaging and neurological examination before surgery and were followed in the postoperative period by repeated neurological examination, imaging surveys, and histopathological studies. Statistical analysis was performed using SPSS program version 23. Results: This study consisted of 59 males and 41 females with a mean age of 45.2 (24-63 years). Visual field defect (48%) was the most frequent finding, while asymptomatic status (36%) was the second major clinical finding in the patients. Neuroimaging survey revealed small tumor size and low extension type in 39 and 40 patients, respectively. Following the trans-sphenoid surgical approach, intact adrenal, gonadal, and thyroid function was found in 92%, 92%, and 89% of the postoperative phase cases. In the postoperative period, visual field defects, need for re-operation, diabetes insipidus (DI), focal neurological deficits (FND), diplopia, post-operative hemorrhagic event, cerebrospinal fluid (CSF) leak and meningitis were observed in 15%, 6%, 5%, 4%, 3%, 3%, 2% and 1% respectively. Moreover, three patients expired in the postoperative period. Our statistical analysis identified the presence of headache (P-value 0.039), functional pituitary adenoma(P-value 0.031), abnormal adrenal gland function(P-value 0.028), abnormal thyroid function (P-value 0.003), and abnormal growth hormone (GH) levels (P-value 0.008) as the major relevant contributing factors in determining the clinical status such as radiological imaging studies of the pituitary region, and hormonal profiles of these groups of patients. Conclusion: In general, the current study revealed that headache, as well as the presence of functional pituitary adenoma and abnormal adrenal, thyroid, and growth hormone levels, are among the major contributing factors in the determination of the postoperative clinical status of patients diagnosed with pituitary adenomas underwent trans-sphenoid surgery.